Pengaruh Insentif dan Kepemimpinan Dalam Meningkatkan Disiplin Kerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Banten - Welen Kurniawan (Fakultas Ekonomi dan Bisnis Universitas Prima Graha, 2020)
This study aims to examine the effect of incentives and leadership in improving employee’s work discipline with job satisfaction as an intervening variable. This study uses quantitative and descriptive methods with causality approach. The object of this study is DPMPTSP Banten Province, using a sample of 62 respondents. Questionnaire answers were measured on an interval scale of 1- 10. Analysis data is using SmartPLS software version 3.0. The results showed that incentives had an effect on employee’s work discipline while leadership had no effect on employee’s work discipline. Incentives affect job satisfaction, leadership influences job satisfaction and job satisfaction affects employee’s discipline. Mediation test results showed job satisfaction can mediate the indirect effect of incentives on employee’s work discipline and leadership on employee’s work discipline.